Systematic literature review on social enterprise as poverty reduction strategy during pandemic - Adenan, Nur Zharifah Che; Said, Roshima; Arsad, Syahiza; Noor, Farah Amalin Mohd (Journal of Islamic, Social, Economics and Development, 2025)
COVID-19 exacerbated global socioeconomic challenges, disproportionately affecting vulnerable populations and boosting poverty rates. This pandemic has hampered the sustainability goal set by the United Nations, which is to be achieved by or before 2030. The current study looked at the available literature on social entrepreneurship plans or strategies for reducing poverty caused by pandemics. The study used Web of Science and Scopus, as well as Emerald Insight, Wiley Online Library, and Google Scholar, to perform a systematic review of high-quality journal databases. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis), we discovered 21 articles that were connected. A closer look at these papers uncovered several crucial conclusions, including the significance of social enterprises in poverty alleviation during the current pandemic. As the government and private corporations focus on the health system, which is becoming more immobile due to the influx of COVID-19 patients, our analysis indicated that the role of social enterprises in decreasing poverty is critical. The present literature emphasizes how social enterprises manage their social obligations to the community during the COVID-19 pandemic and using a comprehensive review of empirical data. Furthermore, this research generates ideas for future research investigation. The conclusions of this study are important for researchers, professionals, and regulators that work on poverty reduction programs.